Seated by the Sea: The Maritime History of Portland, Maine, and Its Irish Longshoremen - Bischoff, Peter C. (Labour / Le Travail, 2011)
The article reviews the book, "Seated by the Sea: The Maritime History of Portland, Maine, and Its Irish Longshoremen," by Michael C. Connolly.
Keywords: BOOKS -- Reviews; CONNOLLY, Michael C.; History; Nonfiction; PORTLAND (Me.); SEATED by the Sea: The Maritime History of Portland, Maine & Its Irish Longshoremen (Book)